Factors Affecting Work Motivation of Agricultural Extension Officers of Odisha - Jaya, G (Journal of Agricultural Extension Management, 2019)
Well-trained and highly motivated extension functionaries play a critical role inagricultural development as they provide advisories and extension services to the farming community. This study was undertaken to find the factors that influence work motivation of newly-recruited extension functionaries of Odisha state. In the present study, five different aspects of motivation were studied using relevant statements. The statements are sub-grouped as Achievement motivation, Advancement motivation, Work itself is motivation, Recognition motivation and Growth motivation. The study revealed that extension officers are innovative in thinking and ready to take new and non-routine assignments. When the situation demands, they are ready to take decisions and also take responsibility towards their role in agriculture extension related activities. A significant number of extension officers felt proud of their achievements. The functionaries perceived high score in career development than monetary benefits. They are highly motivated when farmers recognize and appreciate their work and services.